Posttraumatic Growth: The Role of Trauma Exposure and Family Hardiness Against Pasigala Liquefaction Survivors - Khusnul Khatimah; Sri Redatin Retno Pudjiati (Universitas Medan Area, 2022)
The natural disaster occurred in PASIGALA in 2018 left a significant impact on the survivors of liquefaction. Research on recovery after a disaster focuses on the positive outcomes by survivors. This study aims to determine the role of trauma exposure and family hardiness in developing posttraumatic growth (PTG). Participants in this study were 147 adult survivors (Musia = 23.06, SD = 4.12) spread across Palu City and Sigi Regency, Central Sulawesi. PTG was measured by Posttraumatic Growth Inventory Short-Form (PTGI-SF), trauma exposure was measured by modification of the Earthquake Exposure Questionnaire and Impact of Event Scale, and family hardiness was measured by Family Hardiness Index (FHI). The hierarchical regression test found that trauma exposure and family hardiness significantly predicted 7% and 17.2% of posttraumatic growth variances when other variables were controlled. Then, the mediation test showed that family hardiness had a significant or partial role as a mediator between trauma exposure and PTG. The more trauma exposures experienced by individuals when natural disasters occurred, with a higher level of family hardiness, individuals would achieve a higher PTG condition (c = 0.759, p < 0.01) than if only considering the role of trauma exposure (c' = 0.301, p < 0.01). This shows that family hardiness is an important factor to consider when assisting liquefaction disaster survivors who are exposed to traumatic events in developing posttraumatic growth